Pediatric Obesity and the Liver. Issue 1 (March 2013) - Hardee, Steven; Morotti, Raffaella A.
The obesity epidemic affects both the adult and pediatric populations. Obese children are at risk for comorbidities such as cardiovascular disease and nonalcoholic fatty liver disease (NAFLD). NAFLD is the most common cause of pediatric liver disease and prevalence rates are increasing in parallel to obesity rates. Pediatric NAFLD is a difficult diagnostic entity complicated by lack of accurate noninvasive screening tools. Currently, microscopic liver examination biopsy is the gold standard for diagnosis. Histologically, NAFLD can range from simple steatosis to nonalcoholic steatohepatitis (NASH) and cirrhosis. Pediatric NASH is histologically distinct from typical adult NASH. Type 2 NASH, originally described as the most common pattern of pediatric NASH, is characterized by macrovesicular steatosis, portal tract inflammation, and variable fibrosis without ballooning degeneration or perisinusoidal fibrosis. Type 1 NASH, or adult NASH, is characterized by macrovesicular steatosis, ballooning degeneration, lobular inflammation, and variable fibrosis. Recent studies have shown that overlap patterns between NASH type 1 and 2 are more frequently encountered in the pediatric population. We address the association between pediatric obesity and nonalcoholic fatty liver disease (NAFLD) with discussion of disease demographics, histopathology, and the role of autopsy.